(untitled) (Research, Society and Development, 2020)
Learning the contents of Electronic Distribution and Periodic Table is often considered a difficult process by high school students. Therefore, the purpose of this work was to develop and apply, in high school classes, a didactic game that includes the Electronic Distribution content. The research was developed in three public schools in São Mateus/ES city and had the purpose to verify if the use of this methodology motivates the students achieve learning. As a way of evaluating the methodology, two questionnaires were applied: one before and one after the dynamic class using chemical domino. The results demonstrated the proposal success since it was well accepted by the students. They participated in a playful and active way in the construction process of the concepts related to Electronic Distribution.